Critical Realism and Concrete Utopias. - Archer, Margaret S. (Journal of Critical Realism, 2019)
The role of Concrete Utopias in the works of Roy Bhaskar are contrasted with the 'Real Utopias' of Erik Olin Wright. Critical Realism treats them as 'possibilities' that are real because realizable. Conversely, to Wright, they are extrapolations of existing social forms whose future combination could result in socialism. As such, Bhaskar's philosophical contribution is supplemented by the Morphogenic Approach (Archer) developed for use in the social sciences. 'Real Utopias' are considered to be necessarily Actualist, thus limiting future change in social forms to those that already exist, despite transformation being 'activity dependent'. Critical Realism attaches more importance to structural and cultural constraints and to agential ingenuity in transforming them. In short, Real Utopias are realistic rather than real though preferable to existing social formations, whilst Concrete Utopias allow for new novelty, such as de-growth, giving hope for reshaping global society.